Merit System Inefficacy: Analysis of ASN Vulnerability to Regional Head Authority Post-Elections in Indonesia - Oslita, Oslita; Febrian, Febrian; Ridwan, Ridwan (Journal Public Policy, 2025)
This study examines whether the merit system effectively protects State Civil Apparatus (ASN) from authority abuse by regional heads following local elections in Indonesia. Through normative legal research employing conceptual and statutory approaches, the study critically analyzes the implementation gap between merit system regulations and post-election personnel practices. Document analysis of relevant legislation, administrative court decisions, and semi-structured interviews with KASN members and affected civil servants reveal three key findings. First, the institutional design placing regional heads as both political officials and Civil Service Development Officers creates inherent conflicts of interest that systematically undermine merit principles. Second, oversight mechanisms lack enforcement authority, with KASN recommendations frequently ignored without consequences. Third, post-electoral political dynamics drive personnel decisions based primarily on political loyalty rather than competence, manifesting in systematic bureaucratic reshuffles that disrupt institutional continuity. The research concludes that despite comprehensive legal frameworks, Indonesia's merit system fails to protect civil servants from political interference due to weak enforcement mechanisms and conflicting institutional roles. These findings suggest that structural reforms separating political and administrative functions in civil service management and strengthening oversight institutions with meaningful sanctioning powers are essential for establishing a truly merit-based bureaucracy in Indonesia's decentralized governance system.